2003
DOI: 10.1071/ar02117
|View full text |Cite
|
Sign up to set email alerts
|

Responses of broilers at moderate or high temperatures to dietary arginine:lysine ratio and source of supplemental methionine activity

Abstract: Recent studies have shown that the relative feed intake (FI) and bodyweight gain (BWG) responses of chronically heat-stressed broilers to equimolar additions of DL-methionine (DLM) or 2-hydroxy-4-(methylthio) butanoic acid (HMB; Alimet) can be altered by changing the arginine:lysine (arg:lys) ratio of the diet. However, no information is available concerning responses of broilers during acute heat stress. Broilers were exposed to either 22°C or 30°C during 3 consecutive 5-day experimental periods between 28 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Similarly, the Arg:Lys ratio of 1.05 improved (p<0.05) broiler weight gain and feed conversion. Consistent results were reported in other studies, where an increase in Arg:Lys ratio improved the performance of broilers reared under high environmental temperatures (Brake et al, 1998;Balnave & Brake, 2001;Costa et al, 2001;Chen et al, 2003;Chen et al, 2005). No interaction was detected between tested factors (p>0.05) for live performance parameters.…”
Section: Effects Of Methionine Source Arginine:lysine Ratio and Sodisupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the Arg:Lys ratio of 1.05 improved (p<0.05) broiler weight gain and feed conversion. Consistent results were reported in other studies, where an increase in Arg:Lys ratio improved the performance of broilers reared under high environmental temperatures (Brake et al, 1998;Balnave & Brake, 2001;Costa et al, 2001;Chen et al, 2003;Chen et al, 2005). No interaction was detected between tested factors (p>0.05) for live performance parameters.…”
Section: Effects Of Methionine Source Arginine:lysine Ratio and Sodisupporting
confidence: 91%
“…Balnave et al (1999) observed a progressive decline in weight gain when broilers received DLM in their diet and when the Arg:Lys ratio increased from 1.03 to 1.34. Chen et al (2003) also evaluated the interaction between Met sources and Arg:Lys ratios in diets with DLM and HMTBA and observed an increase in weight gain when broilers were kept under of heat stress conditions with increasing Arg:Lys ratios (1.04-1.19 to 1.35), in the presence of HMTBA, but not of DLM. Balnave & Brake (2004), in a review on the effects of environmental temperature and dietary composition on the effectiveness of DLM and HMTBA, concluded that, in diets with low Arg:Lys ratio (1.05) and high NaCl levels, supplementation with DLM was more effective, while in diets with high Arg:Lys ratio (1.35) and low NaCl levels, performance was better when the diet was supplemented with HMTBA.…”
Section: Effects Of Methionine Source Arginine:lysine Ratio and Sodimentioning
confidence: 99%
“…Derick et al (1999) found that favorable growth responses to HMTBa were evident at higher Arg:Lys ratios (i.e., 1.20 and 1.34), whereas the growth response to DLM was optimized at a lower dietary Arg:Lys ratio (i.e., 1.03). In the experiment of Chen et al (2003), broilers exhibited increased BW gain with increasing Arg:Lys ratio from 1.04 to 1.35 in the presence of HMTBa but not DLM during acute heat stress. The Arg:Lys ratio may become a critical factor that limits growth and may obscure the difference between methionine sources at low dietary CP level.…”
Section: Discussionmentioning
confidence: 90%